Climate change, the media and the knowledge-inaction paradox - Carvalho, Anabela (2012)
The historical era in which we live has been designated as the Anthropocene such is the degree of human intervention on the planet. At a time when the world population has reached 7 billion, we are witnessing a rapid environmental degradation, as suggested by indicators of biodiversity loss, habitat destruction, water scarcity and distribution of pollutants. As a systemic and multi-dimensional problem, climate change stands as a strong symbol of human impact on the environment. Scientific research has shown unambiguously both the anthropogenic nature and the severity of the problem (e.g., IPCC, 2007a), and several recent studies suggest that its impacts could be more devastating than what is indicated by the projections of the Intergovernmental Panel on Climate Change, with the possibility of approaching irreversible „tipping points‟ (e.g. Hansen, 2007; Kiehl, 2011; Shakhova et al., 2010). While the likelihood of large-scale negative impacts of climate change continues to rise and consensus increases around this, various social forces, and policymakers in particular, continue to stall effective transformations to abate GHG emissions.